The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1017/s0014479716000594
|View full text |Cite
|
Sign up to set email alerts
|

COWPEA (VIGNA UNGUICULATA) CROPS IN AFRICA CAN RESPOND TO INOCULATION WITH RHIZOBIUM

Abstract: SUMMARYCowpea (Vigna unguiculata L. Walp) is the most important food grain legume in Africa. Cowpea is nodulated by rhizobium bacteria in almost all soils of the tropics, but studies performed in the 1970s and 1980s in Nigeria suggested only modest responses of grain yield in the field to inoculation of selected rhizobium strains. More recently, experiments performed in Brazil have shown that cowpea responded to inoculation of rhizobium selected locally and grain yields increased by up to 30%. We tested some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 17 publications
5
22
0
Order By: Relevance
“…Increases in grain yields following inoculation of legumes with native rhizobia in this study are remarkable and disprove earlier reports by some authors that these crops do not respond to inoculation with rhizobia (Awonaike et al, 1990;de Freitas et al, 2012;Mweetwa et al, 2014). The results, however, agree with the findings of several authors including Bogino et al (2006), Boddey et al (2016), Ulzen et al (2016), and Martins et al (2003) that inoculating cowpea and groundnut leads to yield improvements. Variations in yield response to inoculation of cowpea and groundnut at the different locations can be attributed to the differences in compatibility between the host plant genotype and specific rhizobium strains under the influence of environmental factors.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Increases in grain yields following inoculation of legumes with native rhizobia in this study are remarkable and disprove earlier reports by some authors that these crops do not respond to inoculation with rhizobia (Awonaike et al, 1990;de Freitas et al, 2012;Mweetwa et al, 2014). The results, however, agree with the findings of several authors including Bogino et al (2006), Boddey et al (2016), Ulzen et al (2016), and Martins et al (2003) that inoculating cowpea and groundnut leads to yield improvements. Variations in yield response to inoculation of cowpea and groundnut at the different locations can be attributed to the differences in compatibility between the host plant genotype and specific rhizobium strains under the influence of environmental factors.…”
Section: Discussionsupporting
confidence: 82%
“…Such stability in performance of test strains in this study makes it easy and convenient to recommend them for inoculant production to increase cowpea and groundnut yields, respectively, with little financial risks for farmers, which will subsequently boost their confidence in the use of the inoculant technology. Several studies have reported on positive yield responses following inoculation of cowpea and groundnut (Martins et al, 2003;Bogino et al, 2006;Boddey et al, 2016;Ulzen et al, 2018), but none of these have considered the stability in performance of the strains. The GGE biplot analyses have been widely employed in the field of plant breeding to identify superior genotypes and for delineation of mega-environments (Yan et al, 2000;Kaya et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Boddey et al . 67 found that inoculation of Cowpea with the Rhizobium strain BR 3299 significantly increased grain yield. Furthermore, as stated in Fan et al .…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, African countries with climate and humidity conditions similar to the North and Northeast of Brazil have tested and observed positive responses to inoculation with elite Bradyrhizobium strains from Brazil. Boddey et al (2016) and Ulzen et al (2016) observed significant increases in nodulation and yield of cowpea inoculated with Brazilian rhizobia in northern Mozambique and northern Ghana.…”
Section: Main Inoculated Cropsmentioning
confidence: 98%